Towards an Alternative Development Management Paradigm? - Shutt, Cathy (Expertgruppen för biståndsanalys (EBA), 2016)
Demonstrating results has been a concern in international development cooperation ever since it was started and in recent years there has been an increased focus on achieving and reporting on “results”. Despite the fact that everyone involved in development cooperation wants to make a difference there has been a growing criticism from practitioners about the “results agenda” based on a concern that the approaches used are not fit for purpose. In the EBA-report, Cathy Shutt, at the University of Sussex, scrutinizes the recent critical debate about results based management, and the main arguments and motives behind the criticism. She shows that the debate is not only a matter of obsessive measurement and reporting of meaningless numbers for political accountability, but also a matter of problematic assumptions and how we think about development, evidence and learning. In the report, Shutt also explores what could be learned from those who are not just critiquing results based management approaches but also proposing alternatives. Are these new alternatives an answer to the criticism?
Keywords: IMPORTANT

SAVI Approach Paper 13: Measuring Value for Money and using Value for Money Analysis - SAVI (DFID, 2016)
SAVI has established its own framework for assessing Value for Money in annual performance – in relation to expenditure, economy, efficiency, effectiveness and equity. Routine tracking and analysis of expenditure and economy ensure that inputs are supplied and services delivered to partners in line with SAVI’s core values, whilst also meeting DFID requirements and competing...